A protocol for in vivo RNA labeling and visualization in tobacco pollen tubes - Kumar, Vinod; Hafidh, Said (STAR protocols, 2024)
Here, we present a protocol for labeling and live visualization of RNA-protein complexes in the form of ribonucleoprotein particles (RNPs) in tobacco pollen tubes. We describe steps for constructing RNA-pp7/MS2 tag and biolistic gene-gun-mediated pollen transformation. We then provide detailed procedures for RNA labeling using PP7 aptamer nascent RNA tagging and a fluorescently labeled Pseudomonas aeruginosa PP7 bacteriophage coat protein (PCP) reporter that binds to PP7 RNA stem loops. This protocol is adaptable to other cell types by employing tissue-specific promoters.
Keywords: plant sciences; pylová láčka; microscopy; Staining and Labeling; Ribonucleoproteins; ribonukleoproteiny; RNA, Plant; Nicotiana; Pollen Tube; tabák; developmental biology; Pseudomonas aeruginosa; RNA rostlin; barvení a značení; cell biology